1981
DOI: 10.1002/art.1780240712
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Pilot Program for Rheumatic Disability in an Urban Community

Abstract: A program for the systematic detection and management of arthritis disability was developed for an urban population. A survey identified 601 persons with rheumatic disability in a population of 9,500-10,550. Seventy-eight persons were evaluated and given recommendations. An ombudsman assisted the clients in obtaining health services and coordinated care. An evaluation 6-8 months later showed increased utilization of and referrals to relevant services but, on the whole, tittle improvement in functional capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Data from the 1979 Health Interview Survey [25] indicate that only 40% of arthritis patients were currently under treatment or medication recommended by a physician. A community study by Liang et al [26] indicated that 30% of persons with arthritis-related functional problems were under no care for them, even though many identified regular physicians. Yelin and Epstein [27] showed that even in areas with significant musculoskeletal disability, community physicians may feel no need for rheumatologists.…”
Section: Fertile Research Areasmentioning
confidence: 98%
“…Data from the 1979 Health Interview Survey [25] indicate that only 40% of arthritis patients were currently under treatment or medication recommended by a physician. A community study by Liang et al [26] indicated that 30% of persons with arthritis-related functional problems were under no care for them, even though many identified regular physicians. Yelin and Epstein [27] showed that even in areas with significant musculoskeletal disability, community physicians may feel no need for rheumatologists.…”
Section: Fertile Research Areasmentioning
confidence: 98%